2021
DOI: 10.1177/02676591211012840
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic respiratory failure and veno-venous extracorporeal membrane oxygenation support

Abstract: Background: Respiratory failure (RF) is a common cause of death and morbid complication in trauma patients. Extracorporeal membrane oxygenation (ECMO) is increasingly used in adults with RF refractory to invasive mechanical ventilation. However, use of ECMO remains limited for this patient population as they often have contraindications for anticoagulation. Study design: Medical records were retroactively searched for all adult patients who were admitted to the trauma service and received veno-venous ECMO (VV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…12,26 While still a relatively new practice, multiple prior studies have explored the feasibility and safety of VV ECMO in the general trauma population. [27][28][29][30][31][32][33][34][35][36] Our study demonstrates that patients with TBI on VV ECMO have similar observed mortality rates as trauma patients without TBI. Survivors in this patient population had largely independent-functioning neurologic outcomes despite presenting with severely depressed GCS.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…12,26 While still a relatively new practice, multiple prior studies have explored the feasibility and safety of VV ECMO in the general trauma population. [27][28][29][30][31][32][33][34][35][36] Our study demonstrates that patients with TBI on VV ECMO have similar observed mortality rates as trauma patients without TBI. Survivors in this patient population had largely independent-functioning neurologic outcomes despite presenting with severely depressed GCS.…”
Section: Discussionsupporting
confidence: 55%
“…Regardless of the pulmonary pathology, VV ECMO is used in patients with respiratory failure refractory to conventional management 12,26 . While still a relatively new practice, multiple prior studies have explored the feasibility and safety of VV ECMO in the general trauma population 27–36 …”
Section: Discussionmentioning
confidence: 99%
“…Dimopoulos et al in their series of patients on V‐V ECMO who received percutaneous tracheostomy showed an ICU mortality of 28% 11 . As reported by Salas et al, 22 both approaches can be considered in patients on ECMO as they display a similar safety profile. No significant differences were reported regarding major bleeding, procedural‐related death, or complication rates (i.e., tracheostomy false track, loss of airway, or tracheal or esophageal injury).…”
Section: Discussionmentioning
confidence: 89%
“…In mechanically ventilated trauma patients, a higher ISS is often associated with a longer duration of mechanical ventilation. [21][22][23] Serum ALB is a nutritional marker that can also in uence the duration of IMV in TBI patients. Low levels of ALB are a useful prognostic marker as they result from increased leakage of albumin from capillaries into the interstitial uid due to systemic in ammatory response syndrome, which has been observed in ICU patients.…”
Section: Discussionmentioning
confidence: 99%